Periodization and sovereignty : how ideas of feudalism and secularization govern the politics of time - Davis, Kathleen, 1952- (Middle Ages series., 2008)
By examining periodization together with the two controversial categories of feudalism and secularization, Kathleen Davis exposes the relationship between the constitution of "the Middle Ages" and the history of sovereignty, slavery, and colonialism.